Effect of visit-to-visit blood pressure variability on mild cognitive impairment and probable dementia in hypertensive patients receiving standard and intensive blood pressure treatment - Guo, Hang; Tan, Yi; Yao, Zhizheng; Zhang, Zilu; Yan, Jiafu; Meng, Xiaofeng (Frontiers in Cardiovascular Medicine, 2023)
Background High visit-to-visit blood pressure variability (BPV) and hypertension are risk factors for mild cognitive impairment (MCI) and probable dementia (PD). Few articles assessed the effect of BPV on the MCI and PD in intensive blood pressure treatment and the different functions of three types of visit-to-visit BPV: systolic blood pressure variability (SBPV), diastolic blood pressure variability (DBPV) and pulse pressure variability (PPV). Methods We performed a post hoc analysis of the SPRINT MIND trial. The primary outcomes were MCI and PD. BPV was measured by average real variability (ARV). The Kaplan-Meier curves were used to clarify the difference in tertiles of BPV. We fit Cox proportional hazards models to our outcome. We also did an interaction analysis between the intensive and standard groups. Results We enrolled 8,346 patients in the SPRINT MIND trial. The incidence of MCI and PD in the intensive group was lower than that in the standard group. 353 patients had MCI and 101 patients had PD in the standard group while 285 patients had MCI and 75 patients had PD in the intensive group. Tertiles with higher SBPV, DBPV and PPV in the standard group had a higher risk of MCI and PD (all p < 0.05). Meanwhile, higher SBPV and PPV in the intensive group were associated with an increased risk of PD (SBPV: HR(95%) = 2.1 (1.1–3.9), p = 0.026; PPV: HR(95%) = 2.0 (1.1–3.8), p = 0.025 in model 3) and higher SBPV in the intensive group was associated with an increased risk of MCI(HR(95%) = 1.4 (1.2–1.8), p < 0.001 in model 3). The difference between intensive and standard blood pressure treatment was not statistically significant when we considered the effect of the higher BPV on the risk of MCI and PD (all p for interaction >0.05). Conclusion In this post hoc analysis of the SPRINT MIND trial, we found that higher SBPV and PPV were associated with an increased risk of PD in the intensive group, and higher SBPV was associated with an increased risk of MCI in the intensive group. The effect of higher BPV on the risk of MCI and PD was not significantly different in intensive and standard blood pressure treatment. These findings emphasized the need for clinical work to monitor BPV in intensive blood pressure treatment.